Morbidity and mortality associated with ESBL Klebsiella pneumoniae infection in different administration routes in albino rats: Morbidity effects of K. pneumoniae in rats - M.Hussein, Ali (Cellular and Molecular Biology, 2025)
Klebsiella pneumoniae is a non-motile, encapsulated, environmental gram-negative bacterium. Once the bacteria have infiltrated the body, they can display substantial degrees of resistance to drugs and virulence. Extended Spectrum Beta-Lactamases (ESBLs) are most typically seen in K. pneumoniae. The objective of this study was to investigate the morbidity and mortality associated with ESBL K. pneumoniae infection in different albino rat administration route groups. Four cohorts of albino rats were acquired and categorized into the subsequent groups: inhalation, oral administration via food, water, and control group. Each group was infected independently and the isolate administration lasted 6 days. The clinical diagnosis revealed the presence of K. pneumoniae infection. Within one day of infection, the inhalation group exhibited the initial clinical signs and symptoms, such as red eyes, coughing, and closed eyelids. Subsequently, the infection was verified through the process of sample cultivation. Additionally, blood clinical findings, including blood tests such as CBC, lipid profile, CRP, and kidney and liver function tests, further supported the confirmation of the infection. The K. pneumoniae isolates had a severe influence on the CBC, liver, and kidney functioning causing elevated liver enzymes, and high RBC levels with impaired kidney functioning. Due to K. pneumonia's affinity for lung tissue, it had the greatest impact in the albino rat inhalation group.